2005
DOI: 10.1007/s10740-005-0065-9
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of thermal radiation of polymer coating containing hollow microspheres

Abstract: The paper deals with the effect of hollow microspheres added to paint or another polymer coating for open surfaces of a building on the heat loss due to thermal radiation. An approximate theoretical model is suggested, which is based on the spectral calculation of the radiative characteristics of a disperse system and determination of the integral flux of thermal radiation. Calculations are performed for a layer of paint with hollow glass microspheres. It is demonstrated that the microsphere shell thickness ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…When the polymer layer dries out, the distance between the microspheres decreases differently in different directions. This results in the anisotropy of the volume concentration of microspheres and in the respective anisotropy of the radiative characteristics of the medium [2]. The estimates showed that this effect is not significant and we assume the composite material to be homogeneous and isotropic.…”
Section: Samples Of Composite Materials and Experimental Proceduresmentioning
confidence: 95%
See 4 more Smart Citations
“…When the polymer layer dries out, the distance between the microspheres decreases differently in different directions. This results in the anisotropy of the volume concentration of microspheres and in the respective anisotropy of the radiative characteristics of the medium [2]. The estimates showed that this effect is not significant and we assume the composite material to be homogeneous and isotropic.…”
Section: Samples Of Composite Materials and Experimental Proceduresmentioning
confidence: 95%
“…The efficiency factors Q a , Q tr s can be calculated by the Mie theory generalized to the case of refracting and absorbing medium as described in paper [2]. In the monodisperse approximation, which is often used in engineering calculations [12], Eq.…”
Section: Theoretical Modelling Of Directional-hemispherical Charactermentioning
confidence: 99%
See 3 more Smart Citations